Effect of biodiesel waste on brick absorption and strength - Thomas Tan; Habib Musa Mohamad; Hidayati Asrah; Andrew Whyte (Semarak Ilmu Publishing, 2025)
This study investigates the use of the spent bleaching earth pozzolanic, a byproduct of biodiesel production, as a sustainable partial substitute for a cement into cement sand bricks. Growing environmental concerns, along with waste disposal challenges and high carbon emissions from traditional cement, underscore construction industry’s need for eco-friendly alternatives. Spent bleaching earth pozzolanic offers a potential solution, enhancing the brick performances while addressing these issues. The purpose of this research is to assess how varying spent bleaching earth pozzolanic content (10%, 20%, 30%, 40%, and 50%) impacts key properties of cement sand bricks, aiming to identify the optimal replacement level for the structural applications. Laboratory evaluations conducted to analyze the testing of moisture content, water absorption, wet and dry density, initial rate surface absorption (at 1 to 3 minutes), and compressive strength in both wet and dry states. Results demonstrated that cement sand bricks with 20% SBEP replacement performed the best. Specifically, these bricks showed moisture contents are between 134 and 245 grams, water absorption from 5.1% to 9.4%, wet densities ranging from 2444 to 2840 grams, and the dry density of 1.8 kg/m³. Initial rate surface absorption between 0.27 and 2.2 g/mm²/min, while the compressive strengths reached 7.1 MPa (wet) and 8.6 MPa (dry). The findings indicate that incorporating 20% spent bleaching earth pozzolanic into cement sand bricks produces eco-friendly, load-bearing bricks with sufficient structural integrity. Research highlights spent bleaching earth pozzolanic potential as an alternative material supports sustainable construction by reducing waste, environmental impact while maintaining material performance. This study contributes valuable insights into the feasibility of the spent bleaching earth pozzolanic as partial cement substitute, advancing the sustainable development in the construction industry.